The Dialectic of Religiosity and Local Traditions in the Dynamics of Community Life A Study of the Anthropology of Religion - Miftahul Huda; Faiqatul Husna (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
Abstract Religiosity and local traditions are two fundamental elements that shape the dynamics of community life. Their relationship is not static but continuously evolves through interaction, adaptation, negotiation, and transformation influenced by social, cultural, and historical changes. Previous studies have generally examined religious practices and local traditions separately, while comprehensive discussions on their dialectical relationship from the perspective of the anthropology of religion remain limited. This gap highlights the need for research that explains how religiosity and local traditions interact in constructing community values, identities, and social practices. This study aims to analyze the dialectics of religiosity and local traditions within the dynamics of community life from the perspective of the anthropology of religion. It further seeks to explain the processes of interaction, adaptation, negotiation, and transformation that occur between religious values and local traditions in society. Accordingly, this study is expected to provide a more comprehensive understanding of the relationship between religion, culture, and social change in community life. This research employs a qualitative approach using a library research method. The data were collected from scholarly sources, including books, journal articles, conference proceedings, and other relevant literature concerning religiosity, local traditions, the anthropology of religion, and community dynamics. Data were analyzed through identification, classification, reduction, interpretation, and synthesis of previous studies to generate a systematic understanding of the interaction between religiosity and local traditions. The findings reveal that religiosity and local traditions have a dialectical relationship that continuously shapes community life. Their interaction occurs through adaptation, negotiation, and transformation without eliminating the essential identity of either element. Local traditions function not only as cultural heritage but also as a medium for expressing and preserving religious values within society. Social change and technological development do not necessarily diminish local traditions; instead, they encourage the emergence of new forms of practice rooted in both religious and cultural values. The study concludes that the anthropology of religion provides a comprehensive analytical framework for understanding the interaction between religiosity and local traditions within community dynamics. This research contributes to the development of the anthropology of religion by offering a broader conceptual understanding of the interaction, adaptation, negotiation, and transformation between religion and culture as the foundation of social identity and community cohesion. Keywords: Religiosity; Local Tradition; Anthropology of Religion; Community Dynamics; Culture.